The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s00115-022-01306-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-Syndrom – Fokus Fatigue

Abstract: Die Weltgesundheitsorganisation (WHO) definiert Post-COVID-19(„coronavirus disease 2019“) als Zustand, der bei Personen mit einer anamnestisch wahrscheinlichen oder bestätigten SARS-CoV-2(„severe acute respiratory syndrome coronavirus type 2“)-Infektion 3 Monate nach Beginn der COVID-19-Symptome und mindestens 2 Monate andauernd vorhanden ist und durch eine alternative Diagnose nicht erklärbar ist. Kernsymptome des Post-COVID-Syndroms umfassen Atemnot, Fatigue und kognitive Dysfunktion, welche das alltägliche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…Previous studies have shown that fatigue constitutes the most important complication after COVID‐19 (Chen et al., 2022 ; Hellwig & Domschke, 2022 ), in both hospitalized and non‐hospitalized patients (Petersen et al., 2021 ). In a meta‐analysis of 19 studies, it was found that fatigue was reported by one third of individuals with the SARS‐CoV‐2 infection at any time point (Healey et al., 2022 ); however, according to some systematic reviews, its prevalence could be even higher, with more than 50% of affected patients (Lopez‐Leon et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that fatigue constitutes the most important complication after COVID‐19 (Chen et al., 2022 ; Hellwig & Domschke, 2022 ), in both hospitalized and non‐hospitalized patients (Petersen et al., 2021 ). In a meta‐analysis of 19 studies, it was found that fatigue was reported by one third of individuals with the SARS‐CoV‐2 infection at any time point (Healey et al., 2022 ); however, according to some systematic reviews, its prevalence could be even higher, with more than 50% of affected patients (Lopez‐Leon et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given a successful evaluation in further studies, such medication may enter the guidelines for the treatment of post-COVID in certain risk groups. Along the same lines, there is meta-analytical evidence suggesting that patients with tumor-associated fatigue benefit from treatment with stimulants and antidepressants (Tomlinson et al, 2018;Hellwig & Domschke, 2022). Also, other treatment methods, for example cognitive behavioral therapy seem to have an effect on both chronic depression (Hofmann et al, 2012) as well as chronic fatigue, especially in the presence of comorbid depression (Castell et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Hossain et al (2020) highlighted the high burden of mental health problems associated with COVID-19, including depression, anxiety disorders, stress, and other psychological impacts. Hellwig & Domschke (2022) discussed post-COVID syndrome with a focus on fatigue and neuropsychiatric late sequelae commonly observed in COVID-19 patients. A systematic review of the association between emotional eating and mental health during the pandemic was carried out by Burnatowska et al (2022).…”
Section: Promoting Physical Activity For Mental Health During and Aft...mentioning
confidence: 99%